2019
DOI: 10.1007/s40430-019-1604-3
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of convective conditions for flow of Oldroyd-B nanofluid by a stretching cylinder

Abstract: As an emergent expertise, there is a serious necessity for enhancing the low thermal conductivity of conventional liquids is to improve proficient heat transfer liquids in numerous solicitations. By diffusing nanometric materials in a certain base liquid, this obligation can be attained and resulting nanoliquid improved the thermal conductivity of the base liquids. Nanofluids are liquid interruptions of nanomaterials, and broad scrutiny has been escorted on nanoliquid solicitations in heat transfer development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[31] scrutinized the Darcy-Forchheimer dusty hybrid nanofluid flow past a cylinder and have concluded that the growth in the fluid motion interaction factor has declined the gradient in velocity for the fluid phase and upsurge velocity for the dust phase. Khan et al [32] observed the output of convective heat transmission upon the nanofluid flow over a stretching cylinder. It has been highlighted in this study that the Deborah number has augmented the flow and has declined the heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…[31] scrutinized the Darcy-Forchheimer dusty hybrid nanofluid flow past a cylinder and have concluded that the growth in the fluid motion interaction factor has declined the gradient in velocity for the fluid phase and upsurge velocity for the dust phase. Khan et al [32] observed the output of convective heat transmission upon the nanofluid flow over a stretching cylinder. It has been highlighted in this study that the Deborah number has augmented the flow and has declined the heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…Bees et al 35 investigated “bioconvection”, which depicts hydrodynamic unsteadiness and examples of living body liquids. Khan et al 36 examined the logical formation of silver nanoparticles over a given base liquid and the resulting nanofluids that create the base liquids’ warmth limit. Tlili et al 37 investigated the slip and activation-energy activities of Oldroyd-B nanofluids during bioconvection.…”
Section: Introductionmentioning
confidence: 99%
“…Crane in 1970 worked on boundary flow over stretching sheets. Some recent developments on stretching surface can be seen in the articles Malik et al; Malik, Khan, and Salahuddin; Alarifi et al; Khan et al; Sohail et al; Khan and Khan; and Khan et al Irfan et al examined the unsteady Carreau nanofluid and found dual solution with the effect of chemical reaction. Different from the above work, the flow on a shrinking surface was considered by Miklavcic and Wang .…”
Section: Introductionmentioning
confidence: 99%